The Influence of School Based Management and Work Motivation towards Teacher’s Performance - Mochammad Sultoni; Bukman Lian; Mulyadi Mulyadi (Universitas Bengkulu, 2020)
This study was to determine whether there was an influence of school-based management (SBM) and work motivation on the teacher’s performance of SD Negeri in Pulau Rimau. The method used was descriptive quantitative. The population used was 19 public elementary schools in Pulau Rimau and the sample was 3 schools. Data were collected using questionnaires and documentation. The results showed that there is significant influence between school-based management (SBM) and work motivation together on teacher’s performance.